Inspiring young minds : scientific inquiry in the early years - Smart, Julie (Writer of educational textbooks) (St. Paul, MN : Redleaf Press, 2017)
'Learn to use inquiry-based practice to inspire young minds through science. This book provides educators a concrete guide for using research-based principles of inquiry to help children explore their world. Using real-life examples and discussions on facilitating and guiding children, you will be able to engage and maximize STEM learning. This book uses case studies to focus on the teacher's interaction with children and includes how to use inquiry-based practice, in addition to why you should use this method. Web content and reproducible lesson plans make it easy to begin using proven inquiry-based instruction. Detailed accounts of conversations with children about science will help you understand different methods and tools. Enrich and inspire young minds with inquiry-based instruction. Julie Smart holds a PhD in curriculum and instruction and is currently a professor of math and science education at Clemson University. She is also a consultant in research methodology and program accreditation with a focus on inquiry-based instruction, teacher effectiveness, and classroom management. Smart resides in Greenville, SC, with her husband and two children'--
'Inquiring Young Minds provides teachers of young children with a concrete guide for using research-based principles of inquiry to help children explore their world. Each chapter in the book provides a real-life example of children exploring a specific topic in science, followed by a discussion of the critical ideas related to facilitating and guiding children in their natural exploration of the world around them'--
Includes bibliographical references and index.
Keywords: Science -- Study and teaching (Elementary).; Inquiry-based learning